The validation of urea determination in saliva using optical urea biosensor with p-dimethylaminobenzaldehyde (DMAB) reagent - ALDIANSYAH, TEUKU; SAFITRI, EKA; GINTING, BINAWATI; NAZARUDDIN, NAZARUDDIN; SUHUD, KHAIRI; SALEHA, SITTI; NURHAYATI, NURHAYATI; NAZARUDDIN, SALSABILLA LATANSA; AFIFI, MUHAMMAD RIDHO; NURHAIDA, NURHAIDA (Jurnal Natural, 2025)
The validation of urea determination in saliva using the biosensor method and the p-dimethylaminobenzaldehyde (DMAB) method has been successfully conducted. Anthocyanin compounds from Chatarantus roseus flowers were extracted using the maceration method with methanol as the solvent, yielding a total of 22.60% with a total concentration of 6.01 mg/L. The obtained extract was subjected to qualitative anthocyanin testing, showing a positive result was indicated by the formation of a reddish color and quantitative testing with the formation of a faded yellow color. The maximum wavelength ( max) of anthocyanin was 664 nm with an absorbance of 0.674. The saliva samples were obtained from three different ages i.e: children, teenagers, and adults. During the saliva collection procedure, participants were instructed to abstain from consuming any food or beverages, with the exception of water, for a minimum of 1 hour prior to sample collection. All samples were stored in a freezer at 4-8C until needed for analysis. Linearity test results were assessed using a calibration curve, yielding a coefficient of determination (R) of 0.978 with a sensitivity of 0.033 for the biosensor and an R of 0.975 with a sensitivity of 0.685 for DMAB. The limit of detection (LOD) values were determined as 7.203 10 M for the biosensor and 6.984 10 M for DMAB, while the limit of quantification (LOQ) values were 2.182 10 M and 2.116 10 M, respectively. Statistical analysis using a t-test showed tcalculated = 1.314, compared to ttable = 4.302, indicating that tcalculated ttable. This result suggests no statistically significant difference between the biosensor and DMAB methods, confirming that the biosensor method is comparable in performance to the DMAB method. Additionally, urea concentration measurements showed that adult samples exhibited the highest urea levels among the tested samples, which may indicate an association with potential health risks, including dental caries, kidney failure, and liver damage.